Tourism Impacts and Sustainability - Cruz, Reil G. (Manila, 2016)
This book was thus written to address the need for an affordable, easy-to-use, organized, and locally contextualized textbook on the subject. It consists of ten chapters, presented in outcome-based education (OBE) format, with discussion questions, activities, and quiz at the end of each chapter.
Keywords: Sustainable Tourism